PEMANFAATAN SAMPAH MENJADI DEKORASI BUNGA GUNA UNTUK MEMINIMALISIR SAMPAH DAN MENINGKATKAN PENDAPATAN EKONOMI SAMPINGAN PADA IBU-IBU PKK DI DUSUN PAELOAN DESA SUMBERBARU - Lilit Biati; Ridwan; Arif Hariyanto (LP2M Universitas Ibrahimy, 2020)
the use of plastics can provide convenience and practicality, plastic also has a particularly bad impact on the environment. Plastics contain artificial inorganic materials which are composed of chemicals that are dangerous enough for the environment. This waste of plastic is very difficult to decompose naturally. To decompose plastic waste itself, it takes approximately 80 years to completely degrade. Currently the government is increasingly active in providing awareness to the public to reduce the use of plastics in life, then providing teaching on how to treat plastic waste into goods that are beneficial to life. Participatory action research has three word elements, all of which have a connection between Participation, Action and Research. In the process of carrying out social change for the better, it must involve all levels of society who are the object or target as well as the subject where the social change must be carried out. utilization of organic waste which can be used as various kinds of valuable creativity and has a selling price that can improve the community's economy, and also make the environment clean and healthy. Making society in a harmonious and peaceful environment. There won't be any problems. The village will be safe and secure.